HCI Practices in Malaysia: A Reflection of ICT Professionals’ Perspective - Idyawati, Hussein; Murni, Mahmud; Wee, Alvin Yeo (2010)
Although Human Computer Interaction (HCI) has been practised by Western countries over the last 40 years, very little is known about how HCI is being incorporated in Malaysian practices. We undertook a 12-week ethnographical study aimed at revealing HCI perceptions at different managerial levels in Information and Communication Technology (ICT) departments and agencies in Malaysia. We describe and discuss the factors that either drive or impede technology managers towards HCI awareness, based on the nature of ICT-related/software development in Malaysia. The result of the study indicates that the developers and corporations’ overall perception of HCI is influenced by their national and organizational culture. The lack of emphasis on usable interface design and scarce information regarding user studies and evaluation are major concerns. Within this context of developing countries, the difficulty of creating HCI awareness and adopting usability may be due to the complexity of the government’s bureaucracy systems. We suggest that stakeholders and policy makers such as the Malaysian Communications and Multimedia Commission (MCMC) and the Malaysian Administrative Modernization and Management Planning Unit (MAMPU) are more relevant in influencing and/or reinforcing the incorporation of HCI in the workplace and enhancing the usability of the products and software created in the organization at the managerial level.